Ambiguous Devices: Improvisation, agency, touch and feedthrough in distributed music performance. Issue 1 (April 2021) - Stapleton, Paul; Davis, Tom
Abstract : This article documents the processes behind our distributed musical instrument, Ambiguous Devices . The project is motivated by our mutual desire to explore disruptive forms of networked musical interactions in an attempt to challenge and extend our practices as improvisers and instrument makers. We begin by describing the early design stage of our performance ecosystem, followed by a technical description of how the system functions with examples from our public performances and installations. We then situate our work within a genealogy of human–machine improvisation, while highlighting specific values that continue to motivate our artistic approach. These practical accounts inform our discussion of tactility, proximity, effort, friction and other attributes that have shaped our strategies for designing musical interactions. The positive role of ambiguity is elaborated in relation to distributed agency. Finally, we employ the concept of 'feedthrough' as a way of understanding the co-constitutive behaviour of communication networks, assemblages and performers.